Life on the edge: Microbial biomineralization in an arsenic- and lead-rich deep-sea hydrothermal vent - Hu, S.Y.; Barnes, S.J.; Pagès, A.; Parr, J.; Binns, R.; Verrall, M.; Quadir, Z.; Rickard, William; Liu, W.; Fougerouse, Denis; Grice, Kliti; Schoneveld, L.; et al. (ELSEVIER, 2020)
© 2019